The Role of Inflammation and Infection in Age-Related Neurodegenerative Diseases: Lessons From Bacterial Meningitis Applied to Alzheimer Disease and Age-Related Macular Degeneration - Too, Lay Khoon; Hunt, Nicholas; Simunovic, Matthew P. (Frontiers in Cellular Neuroscience, 2021)
Age-related neurodegenerative diseases, such as Alzheimer disease (AD) and age-related macular degeneration (AMD), are multifactorial and have diverse genetic and environmental risk factors. Despite the complex nature of the diseases, there is long-standing, and growing, evidence linking microbial infection to the development of AD dementia. Similarly, there are emerging research findings suggesting a role for parainfection in the pathophysiology of AMD, a disease of the neurosensory retina that has been shown to share risk factors and pathological features with AD. Acute neurological infections, such as bacterial meningitis (BM), trigger inflammatory events that permanently change how the brain functions, leading to lasting cognitive impairment. Neuroinflammation likewise is a known pathological event that occurs in the early stages of the chronic age-related neurodegenerative diseases AD and AMD and might be triggered as a parainfectious event. To date, at least 16 microbial pathogens have been linked to the development of AD; on the other hand, investigation of a microbe-AMD relationship is in its infancy. This mini review provides a brief overview of the existing evidence indicating a contribution of parainfection in the aetiology of AD and AMD. Furthermore, it describes the major immunopathological mechanisms that are common to BM and AD/AMD. Lastly, it draws insights from the existing literature about potential therapeutic options for BM that might alleviate neurological disruption associated with infections, and which could, by extension, be explored in the context of AD and AMD.